Transitional, fused and/or supernumerary vertebrae in the lumbosacrocaudal region of the spine - A reality in many domestic mammals - C Toader Covasa (Veterinární Medicína, 2024)
The aim of this study was to identify the presence of transitional lumbosacral and sacrocaudal vertebrae in domestic mammals, to realise a comparative analysis of the localisation and conformation of this abnormal condition. The research included the following species: cattle - 29 specimens, sheep - 32 specimens, horse - 31 specimens, pig - 26 specimens, rabbit - 33 specimens, dog - 89 specimens and cat - 57 specimens. The spine of the animals was analysed post-mortem or radiologically. The investigations revealed the presence of transitional vertebrae as follows: in cattle - 3 cases (8.7%), all being about the lumbarisation of the first sacral vertebra (S1); in sheep - 3 cases (9.37%), two lumbarisation cases of S1 and one caudalisation of S4 (the last sacral vertebra); in horses - 4 cases (12.9%), all about the sacralisation of Cd1 (first caudal vertebra); in pigs - 3 cases (11.53%), two lumbarisation cases of S1 and one sacralisation of Cd1; in rabbits - 3 cases (9.09%), a lumbar supernumerary vertebra (L8) and two cases of caudalisation of S4; in dogs - 4 cases (4.49%), a lumbar supernumerary vertebra (L8) and 3 cases of sacralisation of the last lumbar vertebra (L7 or L8); in cats - 3 cases (5.26%), two sacralisation cases of the last lumbar vertebra and one case of caudalisation of the last sacral vertebra (S3). A strong lumbarisation process was observed in ruminants (especially in cattle), then in pigs, the sacralisation being prevalent in carnivores. The sacrocaudal transitional vertebra was predominant in horses. No evident influence of the sex and age of the animals was observed.